1993
DOI: 10.1177/41.6.8315280
|View full text |Cite
|
Sign up to set email alerts
|

Parenchymal innervation of normal and cirrhotic human liver: a light and electron microscopic study using monoclonal antibodies against the neural cell-adhesion molecule.

Abstract: Hepatic innervation participates in the control of sinusoidal blood flow and in the regulation of certain metabolic functions of the liver. The study of the distribution of hepatic nerves has been hampered by the lack of adequate markers. We therefore tested the value of the neural cell-adhesion molecule (NCAM) as a probe for the study of parenchymal nerves in the normal and cirrhotic human liver. Four antibodies against various epitopes of NCAM were tested by light and electron microscopic immunohistochemistr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 9 publications
2
14
0
Order By: Relevance
“…PGP9.5-, NSE-, synaptophysin, S-100 and N-CAM-immunoreactive nerve fibers were identified in hepatic acini, along sinusoidal walls, in the space of Disse and in the walls of a few terminal hepatic veins. The intra-acinar distribution of nerve fibers was denser in zone 1 in accordance with previous studies [22,29]. The close relationship of intra-acinar nerve fibers with hepatocytes may reflect their influence in the regulation of carbohydrate and lipid metabolism [26], while nerve fiber distribution in portal tracts is likely related to their hemodynamic actions [20].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…PGP9.5-, NSE-, synaptophysin, S-100 and N-CAM-immunoreactive nerve fibers were identified in hepatic acini, along sinusoidal walls, in the space of Disse and in the walls of a few terminal hepatic veins. The intra-acinar distribution of nerve fibers was denser in zone 1 in accordance with previous studies [22,29]. The close relationship of intra-acinar nerve fibers with hepatocytes may reflect their influence in the regulation of carbohydrate and lipid metabolism [26], while nerve fiber distribution in portal tracts is likely related to their hemodynamic actions [20].…”
Section: Discussionsupporting
confidence: 86%
“…While rat and mouse livers have only limited intrasinusoidal innervation, the livers of man and guinea pig show rich intra-acinar innervation [3,4,13,14,19,20]. In human adult liver, afferent and efferent nerve aminergic and peptidergic fibers are distributed unevenly in the acini running along the sinusoidal walls, predominating in the periportal region [29] but also extending to the terminal hepatic venules [4]. Nerve fibers are identified within the space of Disse, between hepatocytes and in close contact with perisinusoidal, endothelial and Kupffer cells [3,4,20].…”
Section: Introductionmentioning
confidence: 98%
“…Immunohistochemical studies have shown that the nerve fibers in the liver parenchyma are reduced or nearly completely absent in cirrhotic liver disease, whereas the nerve fibers in the portal tracts and fibrous septae remain prominent. [74][75][76] These observations are consistent with an impaired Na + -sensitive hepatorenal reflex, but are not consistent with hepatorenal-baroreflex-induced excitation of renal sympathetic nerve activity, because Figure 8 Responses of renal sympathetic nerve activity and urinary Na + excretion to high-NaCl food intake (20 g kg À1 boiled rice containing 0.4 g kg À1 body weight NaCl) given at time 0. Control: sham-operated control dogs.…”
Section: Liver Cirrhosissupporting
confidence: 61%
“…Previous immunohistological studies using human liver specimens have shown that N-CAM is positive in nerve fibers, NK cells, and proliferating bile ductules (Roskams et al 1990;Scoazec et al 1993;Volpes et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…In the liver, N-CAM-positive structures thus far known are nerve fibers and NK cells (Scoazec et al 1993). Nerve fibers are distributed in the portal area and in the liver lobule, making synapses with perivascular smooth muscle cells, stellate cells, and hepatocytes (Bioulac-Sage et al 1990).…”
Section: Introductionmentioning
confidence: 99%